Letters to a writer of color - Anappara, Deepa; Soomro, Taymour (Random House, 2023)
"These seventeen essays by celebrated writers of color start a more inclusive conversation about storytelling and encourage readers and writers to re-evaluate the codes and conventions that have shaped their assumptions about how fiction should be written. Edited by Deepa Anappara, author of Djinn Patrol on the Purple Line, and Taymour Soomro, author of Other Names for Love, this anthology features writers from around the world, from a diversity of backgrounds and across genres, including: American Dirt critic Myriam Gurba, who describes the circle of Latina writers she has always worked within; award-winning novelist Tahmima Anam, who writes about giving herself permission to be funny as an artist of color; and New York Times opinion columnist Mohammed Hanif, who recalls censorship he experienced at the hands of political authorities. Combining memoir with aspects of craft, this book asks readers and writers to be more inclusive not only in what they read, but how they read, and introduces them to diverse storytelling traditions and techniques. Filled with important questions about the state of fiction and what the future might hold, this is a touchstone for aspiring and working writers and for curious readers everywhere"--